Relationship between Urban Form, Socio-Economic, and Demographic With Journey to Work by Train in Sydney, Australia - Putu Alit Suthanaya (Institut Teknologi Bandung, 2010)
Abstract. This study examines journey to work by train in Sydney and the relationship with urban form, socio-economic and demographic variables by using multiple regression model. Train modal share between area located close to and away from a rail station is compared by using analysis of variance. Results of analyses indicate that the proportion using train between area close to and away from rail station is significantly different. Several urban form variables are related to the proportion using train for work trips. However, when socio-economic factors are included in the analysis, car ownership is the main determinant for the proportion using train whilst urban form variable such as density does not have a significant influence. Although urban form variables are not the most important predictor for rail modal share, urban form does influence the proportion using train in different parts of the metropolitan region. The findings support the use of urban form policies to reduce the dependence on car. A variety of non-urban form factors that affect mode choice are also identified. Abstrak. Studi ini menganalisis perjalanan kerja dengan kereta api di Kota Sydney dan keterkaitannya dengan variabel bentuk kota, sosial ekonomi dan demographi dengan model regresi berganda. Penggunaan kereta api antara lokasi yang dekat dan yang jauh dari stasiun kereta api dibandingkan dengan menggunakan analisis varian. Hasil analisis memperlihatkan bahwa proporsi penggunaan kereta api antara lokasi yang dekat dan yang jauh dari stasiun berbeda secara signifikan. Beberapa variabel bentuk kota terkait dengan proporsi pemakaian kereta api untuk tujuan kerja. Akan tetapi, ketika faktor sosial-ekonomi juga disertakan, kepemilikan kendaraan pribadi menjadi faktor yang dominan, sedangkan variabel bentuk kota seperti halnya kepadatan, tidak memiliki pengaruh yang signifikan. Walaupun variabel bentuk kota bukanlah variabel terpenting terkait penggunaan kereta api, tetapi variabel bentuk kota juga mempengaruhi pemakaian kereta api pada bagian-bagian yang berbeda di wilayah kota metropolitan. Temuan dari studi ini mendukung penerapan kebijakan untuk mengurangi ketergantungan pada kendaraan pribadi. Berbagai variabel selain bentuk kota yang mempengaruhi pemilihan moda juga diidentifikasi.